KOMUNIKASI LINGKUNGAN MASYARKAT PEDULI API (MPA) DALAM MENGATASI KEBAKARAN LAHAN DI DESA PAKNING ASAL KABUPATEN BENGKALIS - Linda, Junita Rosa; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Community engagement through the Masyarakat Peduli Api (MPA) is crucial for preventing fires, particularly in fire-prone areas like Pakning Asal Village. Effective environmental communication by the MPA raises public awareness, encourages preventive participation, and fosters cooperation in nature conservation. This study, using descriptive qualitative methods, involved nine purposively selected individuals and utilized in-depth interviews, observation, and documentation. The results indicate that MPA's communication efforts, including community advisories against burning and routine patrols, have been effective. However, the MPA faces physical and social obstacles. Overall, MPA's efforts in environmental communication have successfully promoted community participation in preventing land burning. Keywords: Masyarkat Peduli Api (MPA), Environmental Communication, Land Fires